Understanding the role played by Pension Fund Trustees and Investment Consultants in Responsible Investment Strategies in South Africa - Beja, Bongiwe Andisiwe (Research of GSB, 2019)
Responsible investing (RI) often used as a synonym for Sustainable Investing, is a global phenomenon which simply refers to the integration of environmental, social and governance (ESG) risks and factors when making investment decisions albeit losing conventional financial criteria in making such decisions. This study was undertaken to interrogate and understand the status quo in terms of the ability of two of the key players in the RI market in South Africa, to fulfil their responsibilities in the implementation of responsible investments principles in practice. The participants in focus of the study are firstly, the asset owners being the pension fund trustees in South Africa where the aim is to discover whether trustees in the pension fund industry are well equipped to play their role in implementing responsible investment principles and strategies when performing their fiduciary duties which encompass decisions made around capital allocation, asset manager selection and selection of service providers. Secondly, the service providers being the appointed investment consultants on pension funds in the country where the aim is to discover and articulate the extent of influence and role played by the service providers to the pension fund trustees in the decision-making value chain of the way in which the retirement funds assets are ultimately managed and invested on behalf of the retirement fund. To achieve the above-mentioned aims, online surveys were conducted for both the South African pension fund trustees as well as South African investment consultants. The questions in the survey comprised a combination of open ended and closed ended questions with Likert scales being used. The data was predominantly qualitative in nature and therefore thematic analysis was employed to analyse the data from both sets of surveys conducted. Key findings of this study show that whilst South African pension fund trustees understand and recognise RI implementation as forming part of their fiduciary duty, there is a heavy reliance on appointed services providers particularly investment consultants in terms of their fund’s RI policy and the RI strategies they employ. In order to keep abreast of industry developments in RI and to ensure their funds stay in line with emerging good and best practice, the trustees receive assistance and guidance from their appointed investment consultants. Investment consultants play a significant role on RI matters in that they provide training on ESG and RI implementation to trustees and proactively table RI matters when meeting with the trustees. Many of the consultants however are of the view that training and education of the trustees is pertinent in the uptake of RI in the industry and that this drive must be asset owner led. Based on the results of the study it is recommended that the education of trustees on RI related matters be further investigated. In particular, additional research on the education, the frequency thereof as well as the provider of education is required. The study also highlights the need for further research on the implementation on specifically impact investing as an RI strategy in South Africa. It can also be concluded from this research that global industry bodies such as United Nations Principles for Responsible Investment, CFA Society and local bodies such as Association of Savings and Investments in South Africa, Institute of Retirement Funds Africa, Batseta Council of Retirement Funds in South Africa and the Financial Sector Charter Council could be contributors to a practical policy around asset consultant reliance and trustee education in the implementation of Responsible Investment strategies for all pension funds and their beneficiaries in South Africa.